Life at ultralow interfacial tension: wetting, waves and droplets in demixed colloid-polymer mixtures - Lekkerkerker, H; de Villeneuve, V; de Folter, J; Schmidt, M; Hennequin, Y; Bonn, D; Indekeu, J; Aarts, D (2008)
Mixtures of colloids and polymers display a rich phase behavior, involving colloidal gas (rich in polymer, poor in colloid), colloidal liquid (poor in polymer, rich in colloid) and colloidal crystal phases (poor in polymer, highly ordered colloids). Recently, the colloidal gas-colloidal liquid interface received considerable attention as well. Due to the colloidal length scale the interfacial tension is much lower than in the atomic or molecular analog (nN/m instead of mN/m). This ultra-low interfacial tension has pronounced effects on the kinetics of phase separation, the colloidal gas-liquid profile near a single wall and the thermally induced fluctuations of the interface. The amplitudes of these thermally excited capillary waves are restrained by the interfacial tension and are for that reason of the order of the particle diameter. Therefore, in molecular systems, the capillary waves can only be seen indirectly in scattering experiments. In colloidal systems, however, the wave amplitudes are on a (sub) micrometer scale. This fact enables the direct observation of capillary waves in both real space and real time using confocal scanning laser microscopy. Moreover, the real space technique enables us to demonstrate the strong influence of interface fluctuations on droplet coalescence and droplet break up. © 2008 Springer.